Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50864
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Flow Control to an Aft-Loaded Low Pressure Turbine Cascade With Unsteady Wakes

Abstract: The synchronous application of flow control in the presence of unsteady wakes was studied on a highly-loaded low pressure turbine blade. The L1A blade has a design Zweifel coefficient of 1.34 and a suction peak at 58% axial chord, making it an aft-loaded pressure distribution. Velocity and pressure data were acquired at Rec = 20,000 with 3% incoming freestream turbulence. Unsteady wakes from an upstream vane row are simulated with a moving row of bars at a flow coefficient of 0.76. At this Reynolds number, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The L1A has a Zweifel coefficient of 1.35, which corresponds to 10% higher loading than the "ultra-high lift" airfoils described by Zhang and Hodson [7], and 17% higher loading than the Pack B. Because the L1A is highly loaded and aft loaded, it is prone to separation, as documented in Bons et al [16] and Volino [3]. In cases without flow control and low Reynolds numbers, the boundary layer separates and does not reattach, in spite of transition to turbulence in the shear layer over the separation bubble.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The L1A has a Zweifel coefficient of 1.35, which corresponds to 10% higher loading than the "ultra-high lift" airfoils described by Zhang and Hodson [7], and 17% higher loading than the Pack B. Because the L1A is highly loaded and aft loaded, it is prone to separation, as documented in Bons et al [16] and Volino [3]. In cases without flow control and low Reynolds numbers, the boundary layer separates and does not reattach, in spite of transition to turbulence in the shear layer over the separation bubble.…”
mentioning
confidence: 91%
“…Separation control with VGJs has been demonstrated on the L1A airfoil by Bons et al [16], who considered a case with Re ¼ 50000, background freestream turbulence TI ¼ 3%, and periodic wakes, and by Volino et al [17], who considered cases with TI ¼ 0.6% and documented pressure distributions on the airfoils and total pressure losses. Cases were considered at Reynolds numbers from 25000 to 100000 (10000e40000 based on inlet velocity and axial chord).…”
mentioning
confidence: 98%
“…Nevertheless, the high loss reductions for steady inflow conditions suggest that the usage of fluidic actuators will still be very valuable. Bons et al [23] for example reported that the combination of unsteady wakes with flow control by vortex generator jets could reduce total pressure losses by 60% compared to the case with unsteady wakes only.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the high loss reductions for steady inflow conditions suggest that the usage of fluidic actuators will still be very valuable. Bons et al (2011) for example reported that the combination of unsteady wakes with flow control by vortex generator jets could reduce total pressure losses by 60% compared to the case with unsteady wakes only.…”
Section: Discussionmentioning
confidence: 99%